ESSENTIAL OIL OF Mentha spicata REDUCES THE INITIAL GROWTH OF Corynespora cassiicola in vitro (REVISTA DE AGRICULTURA NEOTROPICAL, 2021)
Synthetic fungicides are one of the control strategies for the most common diseases in agriculture. However, more sustainable strategies are required. Thus, this study evaluates the potential of the essential oils of Cedrela fissilis and Mentha spicata in the in vitro control of the mycelial growth of the pathogen Corynespora cassiicola. The experiment was conducted at the Phytosanitary Laboratory of the Universidade Estadual do Mato Grosso do Sul (UEMS), University Unit of Cassilândia-MS. The essential oils of Argentine Cedar (Cedrela fissilis) and Spearmint (Mentha spicata) were acquired from commerce. A completely randomized design was used with a factorial scheme of two categories of essential oils (Spearmint and Cedar) x 5 concentrations (0, 25, 50, 100, and 200 μL L-1). The data were submitted to the analysis of variance. The means were compared by the Tukey test at 5% probability. Quantitative data were submitted to regression analysis. The fungicide effect was determined by measuring the diameter of colonies (mean of two diametrically opposed measurements, using a caliper, every 72 hours until reaching 216 hours). Spearmint essential oil (M. Spicata) presented higher efficiency than Argentine Cedar essential oil (Cedrela fissilis) on reducing of Corynespora cassiicola growth in the periods between 72 and 144 hours in vitro.